(untitled) (Research, Society and Development, 2021)
Introduction: The school environment is a multidisciplinary and multidisciplinary space, in which all individuals contribute to the construction of knowledge and knowledge, being a favorable place to work on actions that promote health and prevent diseases and injuries. Methodology: This is an experience report of an activity developed in 2019, with teenagers aged 14 years old, entering the first year of high school. The action was designed based on the Streets model, which consists of an educational game about hygiene. Some questions were adapted to the reality and problems of the school. The action planning used the Problematization Theory methodology, based on the tools of popular education and the exchange of knowledge, developed by Paulo Freire. Experience report and discussion: The idealization of the intervention arose from the need to guide students who had just arrived at high school on good hygiene habits. Teachers complained about the precarious hygiene with which students went to school. The activity took place in the form of a scavenger hunt, where the class was divided into two teams and the conductors presented a series of questions about hygiene, which dealt with oral hygiene, hygiene with shoes, school uniforms, armpits, and even with the genital region. Final Considerations: The intervention was designed to strengthen knowledge about hygiene among students, with commitment and social responsibility, since the encouragement of self-care must be linked to the autonomy and protagonism of the subjects.